2019
DOI: 10.37190/abb-01405-2019-02
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of different orthoses on lower extremity kinetics and kinematics during running; a musculoskeletal simulation analysis

Abstract: The current investigation aimed to examine the effects of different orthotic conditions on the biomechanical mechanisms linked to the aetiology of chronic pathologies using musculoskeletal simulation. Methods: 16 male and 20 females ran over an embedded force plate at 4.0 m/s, in five different conditions (medial, lateral, no-orthoses, semi-custom and off the shelf). Kinematics of the lower extremities were collected using an eight-camera motion capture system and lower extremity joint loading also explored us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The full text of 227 studies was retrieved and screened (figure 2). In total, 71 articles were included in the systematic review 25–95. There were 63 within-subject studies (56 healthy individuals, 7 patellofemoral pain), 1 randomised controlled trial in healthy individuals (online supplemental table 2) and…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full text of 227 studies was retrieved and screened (figure 2). In total, 71 articles were included in the systematic review 25–95. There were 63 within-subject studies (56 healthy individuals, 7 patellofemoral pain), 1 randomised controlled trial in healthy individuals (online supplemental table 2) and…”
Section: Resultsmentioning
confidence: 99%
“…We identified 27 studies that reported PFJRF during running 25 26 34 35 38 39 50 52 56–59 61 68 69 74–76 78 80–82 87 90 91 93 94. Pooled peak PFJRF in healthy individuals was 5.2±1.2 BW25 35 38 39 52 56–58 61 68 74 80–82 87 90 94 based on 17 studies and 4.1±0.9 BW in individuals with patellofemoral pain34 38 78 based on three studies during running (figure 3). The average running speed ranged from 2.33 m/s to 4.47 m/s in healthy individuals and 2.77 m/s to 4.00 m/s in individuals with patellofemoral pain.…”
Section: Resultsmentioning
confidence: 99%
“…From a clinical standpoint, it appears that strategies centred around reducing rearfoot eversion are important to the treatment of PFP in both male and female runners. Conservative modalities such as foot orthoses and ankle braces have been shown to mediate statistical reductions in peak ankle eversion in both male and female runners [62,63]. No analyses have been undertaken using ankle bracing, however previous intervention studies have shown foot orthoses to be effective in treating PFP with greater rearfoot eversion angles at baseline predicting orthotic efficacy [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high incidence of ITBS, prophylactic strategies are a key priority for clinical research. Foot orthoses are frequently adopted for the prevention and treatment of running injuries, and a range of orthoses are available (11). Only one investigation has examined the effects of orthoses on ITB strain mechanics, with Day et al showing that neither 7° lateral, 3° lateral, 3° medial or 7° medial wedged orthoses significantly influenced ITB strain (12).…”
Section: Introductionmentioning
confidence: 99%
“…Only one investigation has examined the effects of orthoses on ITB strain mechanics, with Day et al showing that neither 7° lateral, 3° lateral, 3° medial or 7° medial wedged orthoses significantly influenced ITB strain (12). However, there are a variety of commercially available orthoses; typically classified as off-the-shelf, wedged or semi-custom devices, and there has not been any investigation regarding the influence of different orthotic devices on ITB strain characteristics (11).…”
Section: Introductionmentioning
confidence: 99%